Case study: risk and communication coverage limitations in protected areas / M. Adli Mohd Sidi, Norlaila Azura Kosni and Nurul Diyana Sanuddin - Mohd Sidi, M.Adli; Kosni, Norlaila Azura; Sanuddin, Nurul Diyana (Universiti Teknologi MARA Cawangan Pahang, 2020)
This research was conducted to identify the risk and the telecommunication problem at the tropical rainforest in Taman Negara Gunung Ledang, Johor National Park. This research involved the management team of Taman Negara Gunung Ledang, which included the National Park Manager, Former National Park Manager and a Certified Guide for outdoor recreation activities here. Qualitative method had been used via semi structured interviews for data collection. The interviews were conducted separately to avoid the data influence from each interviewee. The findings of this research had identified that some telecommunication system failure exists in Taman Negara Gunung Ledang and this had caused difficulties and it became more critical during rescuing operations involving individuals hiking to the hill top. Besides, telecommunication services were halted in the deep forest and they were unable to make a call and unable to be contacted. In conclusion, communication is a serious issue in the protected forest especially in the national park and an alternative is needed in order to improve the communication system in the national park.